Analisis Kesulitan Siswa Sekolah Dasar dalam Memahami Operasi Hitung Pecahan pada Pembelajaran Matematika di SDN 4 Poso - Nur Fadlun Fadlun; Sukri Sukri; Putri Wulandari; Ni Kadek Yuniasti (Primary School Teacher Education Study Program; Faculty of Teacher Training and Education; Tadulako University, 2026)
This study aims to analyze elementary school students’ difficulties in understanding fraction arithmetic operations in mathematics learning. This research used a descriptive qualitative approach and was conducted at SDN 4 Poso. The subjects of this study consisted of one mathematics teacher and 24 fifth-grade students. Data were collected through observation, interviews, and documentation. The results showed that students experienced conceptual difficulties, procedural difficulties, and difficulties in solving word problems related to fractions. Students still had difficulty distinguishing numerators and denominators, determining equivalent fractions, and solving fraction operations with different denominators. The factors causing learning difficulties included low learning motivation, weak basic mathematical skills, less varied learning methods, and limited use of concrete learning media. Therefore, the use of concrete learning media, contextual learning approaches, and gradual practice is needed to improve students’ understanding of fraction arithmetic operations.